Russia’s foreign language market and some innovative aspects of the university curricula - REINHOLD, NATALYA (International Journal of Language, Translation and Intercultural Communication, 2016)
Basing herself on the local statistics, the author draws an outline of the current state of things in the Russian foreign language (FL) and translation/interpreting (T/I) job market. In particular, she focuses on the issue of compatibility of the market and business demands for the FL and T/I graduates with the respective degree programmes at the Russian institutions of higher learning. Her findings bring up a patchy picture of the state of things in tertiary education (e.g. the out-of-date curricula, the old-fashioned courses, etc. at some institutions, and the dynamic, progressive and innovative developments at other schools). It is on the latter that she focuses primarily. Her case study is the MBA programme in FL/TI, and Business, which was designed at the RSUH institute for the in-service continuing education.